Su alcuni ritorni alla PRL nella letteratura polacca per l’infanzia - Monika Woźniak (Pl.it)
The article analyses how the memory of the PRL (Polish People’s Republic) is present today in Polish children’s texts. Three types of returns to the PRL in children’s literature are identified: the PRL as a theme in autobiographical, educative, and narrative books (new editions), the presence of authors active in the communist period, and finally, the valorisation through reprints of books and graphic projects of the tradition of the Polish illustration for children. The author concludes that young readers do not show much interest in the communist period, and the only successful return to that historical period seems possible through the visual heritage of the “Polish school of illustration”.